Driving Green Marketing in Fashion and Retail - Tarnanidis, Theodore K.; Tarnanidis, Theodore, 1977-; Papachristou, Eyridiki, 1975-; Karypidis, Michail, 1975-; Ismyrlis, Vasileios, 1971- (Hershey, PA : IGI Global Publisher of Timely Knowledge, 2024)
"This book focuses on the effort of clothing/fashion businesses to best articulate the spectrum of green and sustainable digital marketing techniques based on the use of pioneering practices. By integrating these green and sustainable digital marketing techniques, fashion brands can effectively communicate their commitment to eco-friendly mechanisms towards the growing audience of environmentally conscious consumers. The book focuses on the ongoing trends of green and sustainable (digital) marketing techniques in the fashion industry"--
Puan Aimi Nadia binti Ibrahim@Zakaria
Includes bibliographical references and index.
Keywords: Fashion merchandising; Green marketing; Clothing trade -- Environmental aspects